2013
DOI: 10.17221/121/2013-pse
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of copper and zinc in soil and plant within ten-year application of different pig manure rates

Abstract: Fertilization of crops with pig manure is a common practice throughout the world. Nevertheless, due to the relatively high copper (Cu) and zinc (Zn) contents in pig manure, continuous application of pig manure could have negative effects on soil and plant. The study aimed at the impacts of long-term applying different pig manure rates (equivalently 0, 100, 250 and 500 kg total N/ha/year from 2002 to 2008 and 0, 10, 25 and 50 t fresh weight/ha/year from 2009 to 2011, respectively) on Cu and Zn accumulation in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
22
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(24 citation statements)
references
References 24 publications
0
22
0
2
Order By: Relevance
“…Moreover, high average Cu concentration for swine slurry was also observed in England (470.00 mg/kg DM; Nicholson et al 2003). Furthermore, in China according to Xu et al (2013), high average Cu concentration in pig manure was reported (418.42 mg/kg); and Yang et al (2017) ranged the Cu concentration in the swine compost samples from 3.55 to 916.0 mg kg À1 DW.…”
Section: Zn and Cu Content In Faecal Samples For Swine And Cattle Farmsmentioning
confidence: 92%
See 1 more Smart Citation
“…Moreover, high average Cu concentration for swine slurry was also observed in England (470.00 mg/kg DM; Nicholson et al 2003). Furthermore, in China according to Xu et al (2013), high average Cu concentration in pig manure was reported (418.42 mg/kg); and Yang et al (2017) ranged the Cu concentration in the swine compost samples from 3.55 to 916.0 mg kg À1 DW.…”
Section: Zn and Cu Content In Faecal Samples For Swine And Cattle Farmsmentioning
confidence: 92%
“…In general, a wide range of Zn content was observed because many factors can alter the Zn excretion by faeces (the diet, the management, the different regulations). Li et al (2018) reported high average Zn concentration in the solids residue of swine manure (17467.00 mg/kg), and Xu et al (2013) observed a wide range of this element (183.42 to 1126.25 mg/kg) in pig manure in China. According to Yang et al (2017), the range of Zn concentration in the swine compost (containing swine slurry and straw) ranged from 11.80 to 3692.00 mg kg À1 DW in China farms.…”
Section: Zn and Cu Content In Faecal Samples For Swine And Cattle Farmsmentioning
confidence: 99%
“…The loadings of nutrients and non‐nutrient metals with RM and SL were calculated for application rates that would most likely be used in crop production. Swine slurry (unseparated RM) and SL are commonly used as a N source at rates of about 100 kg total N ha −1 yr −1 or slightly higher (Meade et al, 2011; Schlegel et al, 2015; Xu et al, 2013). Thus, a comparison of loadings of nutrients and metals using RM at 100 kg total N ha −1 versus SL at an equivalent rate was made.…”
Section: Methodsmentioning
confidence: 99%
“…A three-course rotation with soybean (Glycine max L.)-maize (Zea mays L.)-maize was conducted in each plot. A more complete description of this experiment field can be provided by Xu et al (2013).…”
Section: Methodsmentioning
confidence: 99%